Toxicokinetics and metabolisms of benzophenone-type UV filters in rats - Jeon, Hee-Kyung; Sarma, Sailendra Nath; Kim, Youn-Jung; Ryu, Jae-Chun (ELSEVIER IRELAND LTD, 2008)
Sunscreens containing UV filters are recommended to reduce damage caused by solar UV radiation. Recently, benzophenone (BP)-type UV filters have become widely used as UV stabilizers in skin-moisturizing products and sunscreen lotions; however, very little information is available regarding the potential harmful effects of prolonged exposure to these compounds. Therefore, we investigated the toxicokinetics and metabolism of BP-type UV filters in rats using gas chromatography-mass spectrometry (GC-.MS). To examine the metabolism of BP-type UV filters, we analyzed the parent compounds BP and 2-hydroxy-4-methoxybenzophenone (HMB). In rats, BP was mainly converted to benzhydrol (BH) and 4-hydroxybenzophenone (HBP) (i.e., type A UV filters). In contrast, HMB was converted into at least three intermediates, including 2,4-dihydroxybenzophenone (DHB), which was formed via o-demethylation and subsequently converted into 2,3,4-trihydroxybenzophenone (THB), and 2,2'-dihydroxy-4-methoxybenzophenone (DHMB), which formed via the aromatic hydroxylation of HMB (i.e., type B UV filters). Next, the toxicokinetic curve for BP showed a peak concentration (C-max) of 2.06 +/- 0.46 mu g/ml at approximately 4 h after BP administration. After a single oral dose of HMB, the Cm, of HMB reached 21.21 +/- 11.61 mu g/ml within 3 h (T-max), and then declined rapidly compared to the kinetic curve of BP. The concentration of these metabolites in rat blood decreased much more slowly over time compared to the parent compounds. Thus, our results indicate that such metabolites might have more significant adverse effects than the parent compounds over the long term. (c) 2008 Published by Elsevier Ireland Ltd.
Keywords: SALMONELLA MUTAGENICITY TESTS; CHEMICALS; BINDING